Comparison of Efficacy and Safety of IV Ferric Carboxymaltose versus IV Iron Sucrose in Pregnancy and Postpartum Anemia - Dr. Irum Shahzadi, Dr. Somayya Virk, Dr. Ayesha Sehar, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Introduction: Ferric carboxymaltose is a safe intravenous drug that is equally effective as the iron sucrose complex,